Business Plan for StartUp Business Mentoring Service - Stephen Jonathan Gustav; Ridwan Sanjaya; Agus Cahyo Nugroho (Journal of Business and Technology, 2022)
Startups in Indonesia are currently experiencing rapid growth, along with an increase in the number of internet network service users and the purchasing power of their consumption. The popularity of online or internet services is able to make Indonesia's market share not only a target market for sales but also a place for startups. Startups are often starting or growing businesses that have recently been started and are synonymous with technology. However, the level of achievement of startups in Indonesia is still low. The failure of a startup is caused by a managerial factor such as lack of experience and a clear vision from the founders of the company, lack of company focus in running the business or running out of funds, and other factors like the absence of market needs (no market need). Based on the above background, further research was made on the development of application service startups that will be designed with a scope at UNIKA Soegijapranata, as UNIKA Soegijapranata has an entrepreneurial forum called the Center for Student Entrepreneurship (CSE). The application development method used is the Waterfall method which has 5 stages, namely defining and analyzing requirements, designing software and systems, implementing and unit testing.The impact of planning the MentorKu application shows that users plan will use the MentorKu application in order to increase productivity in developing startup businesses and plan to use the MentorKu application in the future. This is shown based on the results of statistical tests obtained after conducting a survey of 60 respondents with 5 variables, namely PE, EE, FC, HM where all of these variables were assessed for their correlation with the BI variable or Behavioral Intention.